Объяснение:
а) х² - 8х = 0, х·(х -8) = 0 ⇒ х =0 или х - 8 = 0; х =0 или х = 8.
б. 6х² = 12; х² = 12÷6, х² = 2, х = ±√2
в) 3x² – 48 = 0, 3x²= 48, x² = 48÷3,x² = 16, х = ± 4
г) 6x² – 5x + 1 = 0;D = b²- 4ac = 25 - 4·6 = 24; x = -b ±√D/2a
x1 = 5+√1/12 = 5+1/12 = 6/12 = 1/2, x2 = 5-1/12 = 4/12 = 1/3
д) x² –16x + 71 = 0.D = b²- 4ac =256 - 4·1·71= 256 -284 =-28 - меньше 0 ⇒∅
е) (4x – 3)2 + (3х – 1)(3х+1) = 9
8х -6 +(9х²-3х+3х-1)=9; 8х -6+(9х²-1) =9; 8х -6 +9х²-1-9 = 0; 9х²+8х-16 =0
D = b²- 4ac = 64+4·9·16= 64+576 =640
х1 = -8+√640/18/= -8+8√10/18; х2 = -8-8√10/18
2*.При яких значеннях а рівняння аx² + аХ + 36 = 0 має один корінь?
D = 0⇒ а²-4·а·36 = 0, а²-144 = 0, а²=144, а = ±12
а) 6а²-54x²=6*(а-3х)(а+3х)
б) 81-64c²=(9-8с)(9+8с)
в) 3x²+6xy+3y²=3*(х+у)²
г) 5p²-10p+5=5*(р-1)²
д) (a²-1)²-9a²=(a²-1-3a)(a²-1+3a)
(а-(3+√13)/2)(а-(3-√13)/2)(а-(-3+√13)/2)(а-(-3-√13)/2)
e) (x²-4xy+4y²)-4=(х-2у-2)(х-2у+2)
ж) a⁶-b⁶=(a³)²-(b³)²=(a³-b³)(a³+b³)=(a-b)(а²+аb+b²)*(а+b)(а²-аb+b²)
и) 8m²+16m+8=8*(m+1)²
к) 36 -(x+4)²=(6-х-4)(6+х+4)=(2-х)*(10+х)
л) b-a-a² + b²=(b-а)+(b²-а²)=(b-а)(1+b+а)
м) a⁴-a³+a-1=а³(а-1)+(а-1)=(а-1)(а³+1)=(а-1)(а+1)(а²-а+1)